Assessment of electrical generation potential and viability of gas collection from fugitive emissions in a Tunisian landfill. (July 2015) - Aydi, Abdelwaheb; Abichou, Tarek; Zairi, Moncef; Sdiri, Ali
Abstract: Three different models were used to estimate LFG generation and the collection efficiency of LFG collection systems at the landfill of Jebel Chakir, Tunisia. The feasibility of LFG-to-energy conversion was investigated based on the modelled results. Theoretical results were compared to the collected LFG from the whole site. Large differences were observed between theoretical and measured data, probably because of the models 'assumptions and subsequent inaccuracies. An analysis of the potential conversion of LFG to electric energy shows a total LFG-to-electricity energy of around 255 GWh with a heating value of 4475 kcal/m 3, based on a LFG collection efficiency of 58% (loss of 42%) and an energy efficiency of 33%. The analysis supported the economic feasibility for a 10 MW power plant at the Jebel Chakir landfill. Finally, the results of the investigation of LFG utilization are considered satisfactory in terms of electric energy generation and in terms of mitigation and reduction of greenhouse gas emissions. Highlights: Viability of LFG collection efficiency and its conversion to electricity are studied. Methodology compares LFG measured and calculated from models. According to the model the efficiency of the LFG collection system was proved. The LFG to electricity is attractive in terms of energy saving and GHG reduction.